LITHOSPHERIC ELASTICITY PROMOTES EPISODIC FAULT ACTIVITY - Chéry J.; Vernant P. (My University, 2006)
Based on the agreement between geodetic and geological plate velocities, interplate fault slip rates are usually considered constant over long periods of time. However, measurements made at different time scales on intracontinental faults suggest that slip rate evolves with time. We examine the slip evolution of a fault embedded in an elastic lithosphere loaded by plate motion. We first assume that the fault friction varies due to a climatic cause. Then we show that high fault stress and low lithospheric stiffness favour large variations of slip rate. In the case where fault weakening is controlled by slip rate, we find that high loading velocity leads to a low stress, constant slip rate, while low loading velocity drives the fault slip rate to cycle between high and low values. This suggests that paleoseismic slip rate could overpass the loading velocity but also fall to zero for some period of time. © 2006 Elsevier B.V. All rights reserved.
Keywords: ELASTICITY; FAULT; FRICTION; LITHOSPHARE; SLIP RATE